Non‐transfusion dependent thalassemia is independently associated with higher alloimmunization risk than transfusion dependent thalassemia and would benefit the most from extended red cell antigen‐matching. Issue 9 (14th July 2021) - Ang, Ai Leen; Lim, Chiew Ying; Ng, Weng Yik; Lam, Joyce Ching Mei
Abstract: Background: Alloimmunization prevalence is conventionally used to identify RBCs alloimmunization risk factors among thalassemia patients, but it may be confounded by differences in transfusion exposure especially between non‐transfusion dependent thalassemia (NTDT) and transfusion dependent thalassemia (TDT) patients. To better identify thalassemia patients with high alloimmunization risks, we used cumulative incidence of first alloimmunization as a function of RBCs transfused to compare alloimmunization risks between TDT and NTDT and to evaluate other risk factors. We also proposed practical strategies to prevent alloimmunization in thalassemia. Study Design and Methods: Adult TDT and NTDT patients who had received ≥2 transfusions and no alloimmunization before their first transfusion were included. Alloimmunization was defined as the development of clinically significant alloantibodies. We estimated the first alloimmunization incidence from transfusion by Kaplan–Meier analysis with the horizontal axis expressed as cumulative non‐antigen‐matched RBC units transfused. We compared this incidence between TDT and NTDT, and analyzed for other alloimmunization risk factors and the alloantibody specificities/frequencies. Results: The alloimmunization prevalence was similar between TDT and NTDT (27% vs. 30% respectively, p  = .726). However, for the same transfusion exposure, NTDT had higher alloimmunization incidence than TDT (hazard ratio 8.59, 95% confidence interval [2.25–32.74], p  = .002), independent of age at first transfusion and last follow‐up, gender, and splenectomy. Anti‐E, anti‐c, anti‐Mi a, and anti‐Jk a were most frequent. Discussion: NTDT has the highest alloimmunization risk and would benefit the most from extended RBC antigen‐matching, especially C, c, E, and e. Other blood group antigen‐matching should be guided by the patient/donor disparities and alloantibody frequencies in different populations.